Non-destructive in situ study of “Mad Meg” by Pieter Bruegel the Elder using mobile X-ray fluorescence, X-ray diffraction and Raman spectrometers - Van de Voorde, Lien; Van Pevenage, Jolien; De Langhe, Kaat; De Wolf, Robin; Vekemans, Bart; Vincze, Laszlo; Vandenabeele, Peter; Martens, Maximiliaan P.J. (Spectrochimica acta. Part B: Atomic spectroscopy, 2014)
“Mad Meg”, a figure of Flemish folklore, is the subject of a famous oil-on-panel painting by the Flemish renaissance artist Pieter Bruegel the Elder, exhibited in the Museum Mayer van den Bergh (Antwerp, Belgium). This article reports on the in situ chemical characterization of this masterpiece by using currently available state-of-the-art portable analytical instruments. The applied non-destructive analytical approach involved the use of a) handheld X-ray fluorescence instrumentation for retrieving elemental information and b) portable X-ray fluorescence/X-ray diffraction instrumentation and laser-based Raman spectrometers for obtaining structural/molecular information. Next to material characterization of the used pigments and of the different preparation layers of the painting, also the verification of two important historical iconographic hypotheses is performed concerning the economic way of painting by Brueghel, and whether or not he used blue smalt pigment for painting the boat that appears towards the top of the painting. The pigments identified are smalt pigment (65% SiO2+15% K2O+10% CoO+5% Al2O3) for the blue color present in all blue areas of the painting, probably copper resinate for the green colors, vermillion (HgS) as red pigment and lead white is used to form different colors. The comparison of blue pigments used on different areas of the painting gives no differences in the elemental fingerprint which confirms the existing hypothesis concerning the economic painting method by Bruegel. •In situ, non-destructive investigation of a famous painting by Pieter Bruegel.•Use of a new, commercial available, portable XRF/XRD instrumentation.•Multi-methodological approach: make also use of a mobile Raman spectrometer.•Used pigments and different preparation layers of the painting are characterized.•The verification of two important historical iconographic hypotheses are performed.